2012
DOI: 10.1103/physreve.86.051304
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced alignment and dynamics of elongated granular particles

Abstract: The alignment, ordering, and rotation of elongated granular particles was studied in shear flow. The time evolution of the orientation of a large number of particles was monitored in laboratory experiments by particle tracking using optical imaging and x-ray computed tomography. The experiments were complemented by discrete element simulations. The particles develop an orientational order. In the steady state the time- and ensemble-averaged direction of the main axis of the particles encloses a small angle wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
94
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(123 citation statements)
references
References 30 publications
26
94
3
Order By: Relevance
“…[29] that the relations between orientational order of the rods and alignment angle are very similar to the values found in nematic liquid crystals (see e. g. [129][130][131][132]). Numerical simulations with DEM [29,128] are in good agreement with the experiments. Torque measurements of sheared elongated grains showed that the alignment of the particles reduces friction in the sheared zone.…”
Section: Fig 12supporting
confidence: 72%
See 1 more Smart Citation
“…[29] that the relations between orientational order of the rods and alignment angle are very similar to the values found in nematic liquid crystals (see e. g. [129][130][131][132]). Numerical simulations with DEM [29,128] are in good agreement with the experiments. Torque measurements of sheared elongated grains showed that the alignment of the particles reduces friction in the sheared zone.…”
Section: Fig 12supporting
confidence: 72%
“…Three-dimensional experiments require either the use of invasive observation methods (excavation) or tomographic tools. Extensive quantitative experimental characterizations of the reorientation of elongated particles under shear in a 3D geometry were recently performed by means of optical imaging and X-ray CT [28,29,128]. Grains with different aspect ratios and geometrical shapes were sheared in a cylindrical split-bottom container (Fig.…”
Section: Sheared Grainsmentioning
confidence: 99%
“…In addition it is likely that θ avg for the intruder is increased because it is a singular entity within a mass of cylinders which are analogous to rods/teardrops with an aspect ratio of 1. If the angle of mixtures follows the previously observed trends of inverse proportionality between aspect ratio and θ avg [4][5][6] which was also observed within our tests, it would likely increase the value of θ avg .…”
Section: Resultssupporting
confidence: 53%
“…The inset shows tests at four different macroscopic shear rates, with the same confining pressure, which shows the mean orientation's independence from the shear ratewhich has also been found in previous studies of masses of elongated particles [4][5][6]. The data presented in the results section was gathered at the highest shear rate shown here.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation